Tax-benefit microsimulation modelling in Tanzania: A feasibility study - Vincent Leyaro; Elineema Kisanga; Gemma Wright; Helen Barnes; Michell Mpike (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper presents the findings from a feasibility study on the potential for developing a static tax-benefit microsimulation model for Tanzania. The paper provides an account of the current tax-benefit system in Tanzania and introduces the survey dataset which could function as the underpinning data for the model. The paper concludes with an assessment of the feasibility of producing such a model for Tanzania with reference to personal income tax, indirect taxes, and contributory and non-contributory benefits.
Keywords: E62; H24; I38; 330; tax; benefits; microsimulation; Tanzania